THE EFFECTS OF THE STUDENTS’ PERCEPTION ON LEARNING MEDIA AND PERSONALITY TOWARDS THE STUDENTS’ SPEAKING ABILITY (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2018)
The aim of the research is to know the effects of  the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ perception on learning media   and personality towards the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ speaking ability. The total sample of this research is  82 students. The technique for collecting data of  the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ perception on learning media  and  personality used   questionnaires, and the speaking ability test was acquired from the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ speaking test by having 15- item interview instrument. The research methodology   used is survey,  and technique of data analysis  used  is regression analysis model. The statistic test used F-test, t-test, Rsquare and the data analysis used correlation technique and partial regression. The research findings are 1). There is   significant effects of the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ perception on learning media  and personality jointly  towards the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ speaking ability at English education department students of private universities  in Subang. The significance of regression coefficient equals to  sig.0.000, or 0.000 Ftabel, or 11.555>3.1, or H1 is accepted.  RSquare coefficient equals to  0.226. It means that the variables of the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ perception on learning media  (X1) and personality (X2) jointly can determine or predict the speaking ability (Y) with  contribution 22.6%.  ÃƒÅ½Ã‚Â± equals to 0.05 and n equals to 82.  H1 is rejected. 2). There is  significant effects partially studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ perception on learning media  towards the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ speaking ability at English education department students of private universities in Subang. It declares that the  sig  value of studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ perception on learning media  variable  (X1)  equals to 0.022. It shows that  probability or significance is less than 0,05. The value of t coefficient or  tobserved equals to 2.339, with ttable equals to 1.99. Since tobserved > ttable and the coefficient value of  Sig.< 0,05, H1 is accepted. 3). There is   significant effects partially personality towards the studentsÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢ speaking ability at English department students of private universities in Subang. It turns out that the  sig.  value of the personality variable (X2) equals to 0.001. It shows that probability or sig  is less than 0,05.  The value of t coefficient or  tobserved equals to 3.394, with ttable equals to 1.99. Since tobserved > ttable and the coefficient value of  Sig.< 0,05  here H1 is accepted
Keywords: Learning Media; personality; Students’ Speaking Ability